Individualism and socialism : - Hirai, Atsuko (Council on East Asian Studies, Harvard University, 1986)
Kawai Eijiro was a controversial figure in Japan during the interwar years. Dedicated to the idea that the socialist aspiration for economic equality could be combined with a classical liberal commitment to individual political and civil rights, he antagonized both Marxists and Japanese nationalists. He was hounded by the government as a leftist and brought to trail during World War II.